Mentorship in Midwifery: The Role of Preceptors in Shaping Professional Identity - Sisilia Prima; Martti Tamm; Liis Rannala (Journal of Midwifery History and Philosophy, 2026)
Background. Mentorship is widely regarded as a crucial element in midwifery education, particularly in facilitating students’ transition from academic learning to professional clinical practice. Beyond technical skill acquisition, mentorship plays a significant role in shaping professional identity by influencing how midwifery students internalize professional values, responsibilities, and ethical standards within clinical settings. However, the mechanisms through which preceptors contribute to professional identity formation remain insufficiently explored. Purpose. This study aimed to examine the role of clinical preceptors in shaping the professional identity of midwifery students during clinical placements, with a particular focus on mentorship practices that support identity development. Method. The study employed a qualitative interpretive research design. Data were collected through in-depth interviews, reflective journals, and non-participant observations involving midwifery students and experienced preceptors in clinical learning environments. The data were analyzed thematically to identify recurring patterns related to mentorship interactions and professional identity formation processes. Results. The findings indicate that preceptors exert a substantial influence on students’ professional identity through role modeling, professional validation, reflective dialogue, and the gradual negotiation of autonomy in clinical decision-making. Supportive and consistent mentorship was associated with enhanced self-confidence, ethical awareness, and a stronger sense of professional belonging. Conversely, fragmented or limited mentorship contributed to uncertainty and weaker integration of professional identity. Conclusion. The study concludes that preceptorship functions as a formative relational process that extends beyond clinical supervision. It serves as a critical mechanism in the development of professional identity among midwifery students. Strengthening mentorship structures and enhancing preceptor preparation are therefore essential to fostering resilient, competent, and professionally grounded future midwives.